Status of Leopard (Panthera parnus fusca) in India - Singh, H. S. (Indian Forester, 2005)
Among the Asian countries, the highest population of leopard occurs in India where it is distributed in 28 States and Union Territories. As a result of conservation measures, the population has recovered during last two decades across the country where population was estimated about 9,800 to 10,400 leopards in 2001-02. There is definite trend for the leopard’s abundance and density in different habitats because distribution of the animal in Indian forests reveals that its number declines with increasing moistness and rainfall. Maximum density was observed in semi-arid bio-geographic region, followed by tropical deciduous forests, which have moderate rainfall. The density further declines in semi-moist forests and becomes very low in the moist forests It is also observed that the fragmented forests of reasonable size in hills dotted across the landscape with human habitation and livestock rearing in plains have turned beneficial to leopard, as the smart cat has adapted to the changed situation to harvest good from the villages in night. In the states like Gujarat, Rajasthan, Haryana, Madhya Pradesh, Uttaranchal and Himachal, which support 68% of the total leopard population of the country, the livestock, especially sheep, goats, stray dogs and poultry are abundant in and around the forests. Construction of network of medium and minor dams and also raising irrigated crops like sugarcane benefited the cat, providing both water and’shelter in the critical period, If population is managed below a reasonable limit in high concentration zone where man-leopard conflict is serious and, its growth and dispersal is facilitated in low density areas of the leopard, India can manage a large number of the leopards in the forests across the country under an appropriate management strategy. Analysis of paper also gives some idea about the optimum population density of the cat in Indian forests.